Impact of climate change on the hydrology of a semi-arid river basin of India under hypothetical and projected climate change scenarios - Sujeet Desai (IWA Publishing, 2021)
Climate change impact on the hydrology of the Betwa river basin, located in the semi-arid region of Central India, was assessed using the Soil and Water Assessment Tool (SWAT), driven by hypothetical scenarios and Model of Interdisciplinary Research on Climate version 5 (MIROC5) Global Circulation Model projections. SWAT-Calibration and Uncertainty Programs (SWAT-CUP) was used for calibration and validation of SWAT using multi-site streamflow data. The coefficient of determination, Nash–Sutcliffe efficiency, RMSE-observations standard deviation ratio and percent bias during calibration and validation period varied from 0.83–0.92, 0.6–0.91, 0.3–0.63 and −19.8–19.3, respectively. MIROC5 projections revealed an increase in annual mean temperature in the range of 0.7–0.9 °C, 1.2–2.0 °C and 1.1–3.1 °C during the 2020s, 2050s, and 2080s, respectively. Rainfall is likely to increase in the range of 0.4–9.1% and 5.7–15.3% during the 2050s and 2080s, respectively. Simulation results indicated 3.8–29% and 12–48% increase in mean annual surface runoff during the 2050s and 2080s, respectively. Similarly, an increase of 0.2–3.0%, 2.6–4.2% and 3.5–6.2% in mean annual evapotranspiration is likely during the 2020s, 2050s and 2080s, respectively. These results could be used for developing suitable climate change adaptation plans for the river basin. HIGHLIGHTS SWAT was calibrated at multi-site gauging stations in a semi-arid river basin.; Hypothetical climate change scenarios of Rainfall, Temperature and CO2 was used to assess the basin response.; Surface runoff was sensitive to rainfall change and ET was sensitive to CO2 change.; Surface runoff and ET are projected to increase during the 2050s and 2080s under RCP scenarios.; Climate change adaptation measures were suggested.;